The Role of the Principal in Implementing Learning Innovation: A Qualitative Study at SMP Muhammadiyah 5 Surakarta - Ananda Navisa Fasty Azkia; Mohammad Zakki Azani (FKIP - Universitas Riau, 2026)
Educational institutions are required to continuously innovate to respond to rapid technological development and increasing competition, while maintaining humanistic and cultural values. School leadership plays a crucial role in ensuring that learning innovation is implemented effectively and sustainably. This study aims to analyze the role of the principal in implementing learning innovations and to identify the challenges faced in the innovation process at SMP Muhammadiyah 5 Surakarta. This research employed a qualitative descriptive approach using field research. Data were collected through in-depth interviews with the principal, direct observation of school activities, and document analysis related to learning innovation programs. The findings indicate that the principal plays a central role in driving learning innovation through a servant leadership approach that emphasizes collaboration, teacher empowerment, and student-centered learning. Learning innovations were implemented through the integration of technology-based learning systems, project-based learning, and curriculum enrichment while maintaining Islamic educational values. Internal challenges mainly involved aligning stakeholders’ commitment, while external challenges included parental support and economic limitations. The study concludes that servant leadership contributes significantly to the successful implementation of learning innovations by fostering a supportive school climate, encouraging stakeholder participation, and balancing technological advancement with Islamic cultural values.